Cerebellar Tuberculoma in a Patient with Lung Tuberculosis New Case: A Case Report - Gemilang Khusnurrokhman; Tutik Kusmiati (Faculty of Medicine Universitas Airlangga, 2020)
Background: Tuberculosis (TB) is an infectious disease which can occur in the lungs and extra lung. One kind of extra lung TB is Cerebellum tuberculoma, which is one of rare manifestations form of TB, difficult to diagnosed, because sign and symptom is not specific.Case: A 17-year-old female presented a TB symptoms. She also had contact with her neighbor that was diagnosed with TB. In physical examination there was reduced motor function on her right extremities. Chest radiology revealed opacities in 2/3 superior in the left lung before treatment. Computed Tomography (CT) head scan with contrast showed ring contrast enhancement in left subcortical hemisphere cerebellum with size as 1.8 x 1.8 x 1.7 cm. Multiple lymphadenopathy in right-left upper-aid jugular and lymph node subcentimeter in right of submandibular, right-left lower jugular with varieties of size, the biggest is 1.6 x 1.5 cm. After 6 months treatment the tuberculoma of cerebellum was gone. Conclusion:Cerebellum tuberculoma is a rare presentation of active TB. Radiological imaging plays an important role in the diagnosis and monitoring of the disease. The appereance of tuberculoma on our patient CT showed nodular-enhancing lesion. Intracranial tuberculoma should be treated conservatively, since the majority of these lesions resolve completely with Anti-Tuberculosis Drugs (ATD). Our patient started ATD and the lesions completely disappeared within 6 months. We wanted to present our case due to well-responded to ATD and being an example of atypical presentation of tuberculosis both clinically and radiologically.